1981
DOI: 10.2508/chikusan.52.219
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Rumen Load and Diurnal Eating Pattern of Sheep Fed in Various Time of Access to Feed

Abstract: Four fistulated sheep were offered hay cubes ad lib. for 24, 12, 6 and 3 diurnal eating patterns and the rumen load which were estimated by the torque values of rumen contents were analysed. As the daily time of access to feed was shortened, sheep tried to ingest feed more rapidly with long time for each meal and little rest. However, they could not completely fit their eating activities for given feeding conditions and reduced total daily feed intake. The mean values of daily intake of feed were 2413, 2086, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…Le rôle de l'état de réplétion du RR dans le contrôle de l'ingestion a souvent été étudié par accroissement artificiel de l'encombrement, soit par des vessies remplies d'eau (Campling et Balch, 1961 ;Grovum, 1979), soit par l'introduction de particules indigestibles (Welch, 1967 ;Welton et Baumgardt, 1970) (Aitchison, 1985 (Freer, Campling et Balch, 1962 ;Suzuki, Shinde et Hidari, 1970 ;Faverdin, 1985) et sur moutons (Hidari, 1981 Aitchison et al (1986), Grenet (1987). Cet effet de la prise de nourriture est certainement dû, d'une part à l'activation des fermentations durant le repas (Focant, 1984), ce qui semble confirmé par le fait que ces accélérations des vitesses de disparition soient plus importantes avec le foin de luzerne plus rapidement fermentescible, et d'autre part à l'augmentation du débit réticulo-omasal liée à la prise alimentaire (Buéno, 1975 (Faichney, 1980 ;Poncet et al, 1986 …”
unclassified
“…Le rôle de l'état de réplétion du RR dans le contrôle de l'ingestion a souvent été étudié par accroissement artificiel de l'encombrement, soit par des vessies remplies d'eau (Campling et Balch, 1961 ;Grovum, 1979), soit par l'introduction de particules indigestibles (Welch, 1967 ;Welton et Baumgardt, 1970) (Aitchison, 1985 (Freer, Campling et Balch, 1962 ;Suzuki, Shinde et Hidari, 1970 ;Faverdin, 1985) et sur moutons (Hidari, 1981 Aitchison et al (1986), Grenet (1987). Cet effet de la prise de nourriture est certainement dû, d'une part à l'activation des fermentations durant le repas (Focant, 1984), ce qui semble confirmé par le fait que ces accélérations des vitesses de disparition soient plus importantes avec le foin de luzerne plus rapidement fermentescible, et d'autre part à l'augmentation du débit réticulo-omasal liée à la prise alimentaire (Buéno, 1975 (Faichney, 1980 ;Poncet et al, 1986 …”
unclassified
“…Because of these factors, ruminants raised on dry forage eat large volumes at one time in order to satisfy their nutritional requirements of maintenance and production levels. Therefore, studies of the effects of rumen fill on silage and hay intake in cows and sheep have been carried out as the part of research on factors regulating dry forage intake in ruminants ( Hidari, 1981 ). Campling and Balch (1961) reported that feed intake was decreased when a balloon was inserted into the rumen and inflated with water in cows fed on hay or silage.…”
Section: Introductionmentioning
confidence: 99%
“…Simultanément, on a mesuré le niveau de remplissage du rumen, en générai à un moment fixe de la journée (Jarrige, 1978). Dans un deuxième temps, les auteurs se sont intéressés à l'évolution journalière du contenu ruminal (Tulloh, Hugues et Newth, 1965;Dulphy, Béchet et Thomson, 1975 ;Paquay, de Baere et Lousse, 1971 ;Hidari, 1981 ;Thomson et al, 1985 …”
unclassified